Konsep Etika Islam Dalam Pembentukan Karakter - arin, arin arin (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2018)
Personality is a description of how a person behaves towards the surrounding environment, which can be seen from the habit of thinking, attitudes and interests, as well as a typical life view to have constancy. Because in human life as individuals or social beings, personality always experiences the colors of life. There are times when happy, calm, and happy. However, life experience proves that humans also sometimes experience things that are bitter, restless, frustrated and so on. This shows that humans experience the dynamics of life. Personality reflects a person's behavior. We can know what someone is doing in a particular situation based on our own experience. This is because in many ways, everyone is unique, unique. Therefore we need a kind of frame of reference to understand and explain the behavior of ourselves and others. We must understand the definition of personality and how the personality is formed. For that we need behavioral theories, personality theory so that the usual disorders that arise in the personality of each individual can be avoided. Learning personality is interesting because the dynamics of knowledge about ourselves will automatically increase. This is because the essence of human beings is that which exists and grows with the personality that accompanies every step of his life. Keywords: Ethics, character, personality